Performa dan Kandungan Hormon Triiodotironin Plasma Ayam Broiler Akibat Pengaruh Cekaman Panas di Daerah Tropis - E Kusnadi; F Rahim (Media Peternakan, 2009)
High environmental temperature may cause heat stress in poultry. This may increase water consumption, decrease feed intake and in turn, decrease production and triiodothyronine hormone level. The aim of the experiment was to study performance and plasma triiodothyronine hormone of broilers exposed to heat stress in tropical area. The study used 140 male broilers of 2 weeks of age. The treatment of environmental temperatures were S1A (28.55?1.53 oC) with ad libitum of feeding, S1BT1 (S1 with pair feeding as S2A), S1BT2 (S1 with pair feeding as S3A), S2A (31.07?1.29 oC) with ad libitum of feeding and S3A (33.50?1.17 oC) with ad libitum of feeding. Variables measured were feed consumption, body weight gain, feed conversion and triiodothyronine hormone level of plasma. The experiment design used was a completely randomized design with 4 replications and continued to Duncan test when it was significantly different. The results indicated that feed consumption and body weight gain in S1A, higher than those in S2A and S3A. The body weight gain in S1BT1 higher than those in S2A, and in S1BT2 higher than those in S3A. The level of plasma triiodothyronine hormone in S1, S1BT1 and S1BT2 was higher than those in S2A and in S3A. Key words: heat stress, body weight gain, triiodothyronine hormone